The Values Included in the Textbooks of Social Studies for Upper Elementary Stage in Palestine - Aseel Hayhtam Abu Ghazaleh; Fatmah Iyad Khweis; Khawla Mahmoud Abu Dahouk; Refa Jamal Ramahi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to identify the values in the social studies textbooks for the upper elementary stage in Palestine. Methods: The study relied on a descriptive analytical approach. The study sample consisted of all pages of social studies textbooks for the upper elementary stage (6-8) for the second semester, which include a set of units and lessons except for the introduction, references and questions. The sample was chosen in an intentional way. A list that includes the most important dimensions of values, sub-values, and the content analysis was used. Results: The results of the study show that national values obtained the highest percentages among the values in the three grades. The scientific values in the sixth and seventh grades were the lowest. The general level of the values included in the curriculum of social studies for the higher elementary school grades was acceptable. Conclusions: The study recommends confirming the level of integration among textbooks of social studies and enhancing educational values in the textbooks.